Almost statistical convergence of order of sequences of fuzzy numbers - Karakas, Abdulkadir; Altin, Yavuz; Altinok, Hifsi (Springer, 2016)
In this article, we introduce the concepts of almost -statistical convergence of order and strongly almost -summability of order for sequences of fuzzy numbers. Also, we establish some relations between the almost -statistical convergence of order and strongly almost -summability of order and we define , where is a modulus function and give some inclusion relations.
Keywords: Fuzzy number; Statistical convergence; Modulus function